Pengaruh Amortasi Goodwill Terhadap Kegunaan Informasi Laba - Tri Lestari; zaki baridwan (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to examine the usefulness of earnings and goodwill amortization by comparing the earnings before goodwill and the reported earnings (which include goodwill amortization). In addition, this study also investigates whether goodwill amortization contains incremental value-relevant information. We use 125 firm-year observations selected purposively from 1999 to 2006 of all listed companies in Indonesia Stock Exchange that report goodwill, as our sample. We find that earnings before goodwill amortization explain significantly more of the observed distribution of share prices than do earnings after goodwill amortization. Our result suggests that goodwill amortization does not contain incremental value-relevant information. In other words, it does not have any unique contribution in the relation between earnings and share value.